A Descriptive And Analytical Study Of Artificial Intelligence Applications In Improving The Accuracy Of Pre-Hospital Triage In The Saudi Red Crescent Services (The Review of Diabetic Studies, 2025)
This research aims to investigate the applications of artificial intelligence in improving the accuracy of pre-hospital triage processes in the Saudi Red Crescent Authority services. The study relied on the descriptive analytical approach, where a questionnaire was distributed to a sample of (200) individuals working in the emergency field. The study tool included several axes to measure the effectiveness of artificial intelligence in diagnosing case severity, reducing human error, accelerating decision-making, improving resource allocation, and ensuring the confidentiality of medical data. The results showed that the majority of the sample had positive attitudes toward the use of artificial intelligence, emphasizing its effective role in reducing errors and improving the efficiency of emergency interventions. They also emphasized the need to provide adequate training for paramedics to ensure the safe and effective use of these technologies. Privacy protection also emerged as a key priority for the sample, while some participants expressed concern about the loss of traditional skills due to over-reliance on smart systems. The study recommends expanding the use of artificial intelligence applications in emergency triage systems, while taking into account training and data protection controls.